Generation Z’s Views on Green Financial Solutions in the Light of Primary Research - Baranyi, Aranka; Zsigrai, Hanna (Acta Carolus Robertus, 2023)
The issue of financial awareness has been addressed by a number of researchers over the past decade, and the financial crisis has underlined its high priority. The COVID-19 pandemic has accelerated changes in payment practices, with an increase in cashless payments in the retail sector. Today, we are faced with the crisis caused by the energy crisis, which has prompted the emergence of new innovations. We have to deal with more and more difficulties in a shorter and shorter time, and we have to bear in mind that the resources we use should be available for future generations. Sustainability has become an important component of our challenging lives and is addressed in this study.